Halogenated transition metal phosphate sodium ion battery positive electrode material and preparation method thereof
Through the combination of Lewis acid-base pair regulation and carbon source, the halogen atoms are stabilized in the positive electrode material of halogen transition metal phosphate sodium ion battery, the halogen volatility problem is solved, the electrochemical performance and cycle stability of the material are improved, and the electrochemical performance and cyclic stability of the material are achieved. High energy density and power density improvement.
Patent Information
- Application Number
- CN202411697533.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The existing halogenated transition metal phosphate sodium ion battery positive electrode materials are prone to halogen volatilization during high-temperature calcination, resulting in a decrease in material purity, a decrease in discharge voltage and specific energy, affecting battery performance.
Using the Lewis acid-base pair regulation strategy, the combination of carbon source and Lewis base can stabilize halogen atoms in the material lattice, and the solid phase method and high-temperature sintering technology are used to synthesize the positive electrode material of halogen transition metal phosphate sodium ion battery to ensure carbon The layer is uniformly coated and inhibits the volatility of halogen atoms.
It improves the purity and electrochemical properties of the material, enhances the specific energy, specific capacity and rate performance, extends the cycle stability, and reduces the production cost.
Smart Images

Figure CN119275284A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a sodium ion battery positive electrode material and a preparation method and application thereof, belonging to the technical field of battery material synthesis. Background Art
[0002] Compared with lithium, sodium is extremely abundant and cheap, so sodium-ion batteries (SIBs) have shown advantages in the fields of mid- and low-end electric vehicles, energy storage power stations, etc. Its electrochemical performance depends largely on the cathode material. Among various candidate materials, halogenated transition metal phosphate sodium-ion battery positive electrode materials (chemical formula Na3M2(YO4)2O x X 3-2x ; 0≤x<1.5; M=V, Fe, Ti, Zr; Y=P, S, Si; X=F, Cl, Br) has a considerable theoretical specific capacity, and the supporting effect of polyanions slows down the attenuation of battery cycle performance, and is considered to be a very promising class of SIBs materials. At present, researchers have improved the electrochemical performance of halogenated transition metal phosphate sodium ion battery cathode materials by introducing strongly electronegative halogens. However, it is well known that halogen atoms form easily volatile halogenated hydrogen with H, which overflows in the material lattice. This phenomenon is very easy to occur during high-temperature calcination. This will not only cause the sample purity to decrease, but the generated Na3M2(YO4)3 secondary phase will also reduce the discharge voltage and specific energy, causing a series of negative effects. Therefore, reducing or eliminating the volatilization of halogens is of great significance, which is also very necessary for the large-scale application of SIBs in large-scale energy storage equipment. Summary of the invention
[0003] The present invention aims to solve the problems of poor purity and uneven conductive carbon coating caused by halogen volatilization in the preparation process of existing halogenated transition metal phosphate sodium ion battery positive electrode materials, and provide a halogenated transition metal phosphate sodium ion battery positive electrode material and a preparation method thereof. The preparation method of the present invention improves the purity and electrochemical performance of the halogenated transition metal phosphate sodium ion battery positive electrode material, including specific energy, specific capacity, rate and cycle performance.
[0004] The halogenated transition metal phosphate sodium ion battery positive electrode material of the present invention is composed of a halogenated transition metal phosphate matrix and a conductive layer coated on the surface thereof; the chemical general formula of the halogenated transition metal phosphate is Na3M2(YO4)2O x X 3-2x ; 0≤x<1.5; M=V, Fe, Ti or Zr; Y=P, S or Si; X=F, Cl or Br; the surface coated conductive layer is a carbon layer. The positive electrode material has high purity and stably exerts high working voltage and excellent cycle and rate performance.
[0005] Furthermore, the thickness of the carbon layer is 1 to 8 nm.
[0006] The preparation method of the above-mentioned halogenated transition metal phosphate sodium ion battery positive electrode material is carried out according to the following steps:
[0007] 1. At room temperature, weigh the sodium source, transition metal M source, Y source and halogen source according to the stoichiometric ratio of the halogenated transition metal phosphate and transfer them to a ball mill for 10 min at 150-250 r / min or grind them in a mortar for 20-30 min to perform preliminary mixing to obtain uniform fine powder;
[0008] 2. Weigh the carbon source and mix it with the fine powder of step 1 in a ball mill, and ball mill at a speed of 400-1200r / min for 8-12h to obtain dry material; wherein the carbon source is an organic acid and a Lewis base corresponding to the organic acid; the organic acid is one or more of citric acid monohydrate, anhydrous citric acid and ascorbic acid, the Lewis base of citric acid is ammonium citrate, and the Lewis base of ascorbic acid is ascorbylamine; the selected organic acid can form a carbon source (granular carbon) with a large specific surface area during the carbonization process, which is easier to coat on the surface of the substrate; if glucose is selected in this step, since it is not easy to form a uniform conductive layer on the surface of the phosphate material, the prepared positive electrode material cannot achieve the expected effect. The more important purpose is to introduce the Lewis base corresponding to the organic acid for localized electronic regulation, so that the halogen atoms can be stabilized when the raw materials undergo preliminary pre-reaction;
[0009] 3. Transfer the obtained dry material to a mortar and grind it to obtain a powdered precursor;
[0010] 4. The powdered precursor is transferred to a tubular furnace, pre-sintered in a flowing inert gas stream, and then continued to be heated to 500°C to 700°C for calcination for 5 to 12 hours. Finally, the powdered precursor is naturally cooled to room temperature as the tubular furnace temperature is cooled to obtain a halogenated transition metal phosphate sodium ion battery positive electrode material.
[0011] Furthermore, the transition metal M source described in step 2 is an ammonium salt of transition metal M or an oxide of transition metal M; the Y source is NH4H2YO4 and / or (NH4)2HYO4; the halogen source is NaX and / or NH4X; these raw materials are easy to grind into fine powder to ensure uniform mixing of the raw materials, and form a halogenated transition metal phosphate sodium ion battery positive electrode material with uniform composition through high-temperature calcination.
[0012] Furthermore, during the ball milling process described in step 2, the temperature is maintained at 35-55° C., and the heat preservation process can increase the thoroughness of the solid phase reaction.
[0013] Furthermore, the ratio of the amount of the carbon source in step 2 to the total amount of the transition metal element is 1:0.8-2.5. The purpose is to allow the dispersed carbon source to penetrate well into the gaps of the precursor, play a role in dispersing the precursor particles to prevent agglomeration, and achieve high electronic conductivity.
[0014] Furthermore, the ball milling process described in steps 1 and 2 is carried out in air or argon protective atmosphere, the ball-to-material mass ratio is (10-50):1, and the ball milling medium is agate ball, ZrO2 ball or stainless steel ball. The purpose is to make the carbon source dispersed evenly.
[0015] Furthermore, the pre-sintering temperature in step 4 is 350°C to 450°C, and the pre-sintering time is 3 to 5 hours. The purpose is to fully thermally decompose the carbon source and reduce the volatilization of halogens;
[0016] Furthermore, the heating rate of the pre-sintering in step 4 is 2-10° C. / min.
[0017] Furthermore, the heating rate of the calcination in step 4 is 2-10°C / min.
[0018] Furthermore, the calcination temperature in step 4 is 550° C. to 650° C. and the time is 5 to 8 hours, in order to allow the carbon thermal reduction reaction to proceed fully.
[0019] Furthermore, the inert atmosphere in step 4 is argon, nitrogen or a hydrogen-argon mixture, wherein the volume percentage of hydrogen in the hydrogen-argon mixture is 5% to 10%.
[0020] The beneficial effects of the present invention compared to the prior art are:
[0021] (1) The present invention proposes a simple Lewis acid-base pair control strategy to stabilize the halogen atoms in the material lattice, thereby obtaining a pure phase halogenated transition metal phosphate sodium ion battery positive electrode material. The halogenated transition metal phosphate sodium ion battery positive electrode material is synthesized by a solid phase method and high temperature sintering technology that is easy to control and convenient for large-scale continuous production. The preparation method is simple, easy to operate and has good reproducibility. The present invention selects a suitable combination of carbon source and Lewis acid-base pair to control the local electronic environment and van der Waals force of transition metal and halogen atoms in the synthesis process of halogenated transition metal phosphate sodium ion battery positive electrode material, suppress the inherent volatility of halogen atoms, so as to achieve the purpose of stabilizing halogen atoms in the lattice of halogenated transition metal phosphate sodium ion battery positive electrode material. Finally, the voltage platform corresponding to the constant current charge and discharge curve of this type of material has almost no fluctuation phenomenon, the transition metal element undergoes redox reaction at a higher voltage, and has excellent long cycle performance and high energy density. The sodium vanadium fluorophosphate, a positive electrode material of the halogenated transition metal phosphate sodium ion battery prepared by the present invention, has a suppressed low voltage platform (-3.4V) during constant current charge and discharge, which is beneficial to the improvement of the overall energy density of the battery.
[0022] The present invention prepares sodium vanadium fluorophosphate, a positive electrode material for halogenated transition metal phosphate sodium ion batteries, by a solid phase method. There are only two distinguishable voltage platforms in the discharge curve (about 4.1V and 3.6V, vs. Na + / Na), because the impurity phase after halogen volatilization produces a lower voltage platform (~3.4V, vs. Na + / Na) disappeared. In addition, the low-voltage platform was manifested in the control group, which comes from the secondary phase Na3V2(PO4)3, the presence of which reduces the average discharge voltage and energy density of the positive electrode material full of the battery. The data analysis is as follows: its discharge specific capacity is 119, 113, 110, 107, 101, 95, 89, 83, and 67 mAh / g at rates of 0.2, 0.5, 1.0, 2.0, 5.0, 10.0, 15.0, 20.0, and 30.0C, respectively. The material can be charged and discharged at a high current density for a long time and stably, and a discharge specific capacity of 60 mAh / g is still retained after 3000 cycles at a current density of 10C. In addition, its constant current charge and discharge curve at 0.2C shows that the positive electrode material undergoes an electrochemical reaction of two voltage platforms and only produces a very small voltage polarization.
[0023] (2) The present invention adds a carbon source with coating material and reducing agent functions so that it is uniformly coated on the surface of the material with a thickness in the range of 1 to 8 nm. A Lewis base matching the carbon source is introduced to generate uniform intermolecular interaction forces through the Lewis acid-base pair, so that the carbon source is more evenly distributed in the precursor material, thereby being more inclined to obtain an electrode material with a uniform and dense carbon conductive layer on the surface. There are two ways: one is to select a Lewis acid-base pair during the preliminary pre-solid phase reaction to regulate the intermolecular interaction during the preparation process, and to assist with heat preservation treatment during the ball milling process to make the solid phase reaction more thorough; the other is to change the type of carbon source. Different carbon sources exist in different forms on the surface of the matrix halogenated transition metal phosphate positive electrode material. An organic acid that is easy to form a uniformly coated carbon conductive layer on its surface is selected as the carbon source to improve its electronic conductivity. In addition, using an organic acid as a carbon source and introducing the corresponding Lewis base can achieve a more stable, dense and highly electronically conductive conductive carbon coating through simple intermolecular forces, so the halogenated transition metal phosphate positive electrode material exhibits better electronic conductivity and significantly improved rate performance.
[0024] (3) The present invention provides a method for preparing a large number of stable high-voltage and high-specific-energy halogenated transition metal phosphate sodium ion battery positive electrode materials, including fine-tuning of local electronic structure, selection of carbon source, synthesis conditions, process parameters and operation methods. A carbon source with high electronic conductivity is used, and the halogen atoms are stabilized by introducing a Lewis base corresponding to the corresponding carbon source, thereby obtaining a high-purity phase of the positive electrode material, and finally significantly improving the electrochemical performance of the material.
[0025] (4) The present invention does not require the use of a dispersant during the preparation process but directly performs dry solid-phase ball milling, thereby reducing the production cost and, more importantly, preventing more complex side reactions in the liquid state (such as various complex reactions) and preventing the volatilization of halogens, such as fluorine. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 XRD spectra of sodium vanadium fluorophosphate prepared in Comparative Example 1 and Example 1;
[0027] Figure 2 This is a rate performance diagram of sodium vanadium fluorophosphate prepared in Comparative Example 1 in a half-cell with sodium as the counter electrode;
[0028] Figure 3 This is a cycle performance diagram of sodium vanadium fluorophosphate prepared in Comparative Example 1 at a current density of 10.0C in a half-cell with a sodium counter electrode;
[0029] Figure 4 The constant current charge-discharge curve of sodium vanadium fluorophosphate prepared in Comparative Example 1 at 0.2C in a half-cell with sodium as the counter electrode;
[0030] Figure 5 This is a rate performance diagram of sodium vanadium fluorophosphate, a positive electrode material of a halogenated transition metal phosphate sodium ion battery prepared in Example 1, in a half-cell with a sodium counter electrode;
[0031] Figure 6 This is a cycle performance diagram of sodium vanadium fluorophosphate, a positive electrode material for halogenated transition metal phosphate sodium ion batteries prepared in Example 1, at a current density of 10.0C in a half-cell with a sodium counter electrode;
[0032] Figure 7 This is the constant current charge and discharge curve of sodium vanadium fluorophosphate, a positive electrode material for a halogenated transition metal phosphate sodium ion battery prepared in Example 1, at 0.2C in a half-cell with sodium as the counter electrode.
[0033] Figure 8 This is a scanning electron microscope image of sodium vanadium fluorophosphate prepared in Comparative Example 1 in a half-cell with sodium as the counter electrode.
[0034] Fig. 9 This is a SEM image of the sodium vanadium fluorophosphate, a positive electrode material for a halogenated transition metal phosphate sodium ion battery prepared in Example 1, in a half-cell with sodium as the counter electrode.
[0035] Fig.10 This is a transmission electron microscope image of sodium vanadium fluorophosphate prepared in Comparative Example 1 in a half-cell with sodium as the counter electrode.
[0036] Fig.11 This is a TEM image of sodium vanadium fluorophosphate, a positive electrode material for a halogenated transition metal phosphate sodium ion battery prepared in Example 1, in a half-cell with sodium as the counter electrode. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention that does not depart from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0038] Comparative Example 1: This example is to prepare sodium vanadium fluorophosphate as a control, whose chemical formula is Na3V2(PO4)2F3. The preparation method of the material is carried out according to the following steps:
[0039] 1. At room temperature, weigh 0.9540g of anhydrous sodium carbonate, 1.4038g of ammonium metavanadate, 1.3800g of ammonium dihydrogen phosphate, and 0.6667g of ammonium fluoride according to the stoichiometric ratio of Na3V2(PO4)2F3 and transfer them to a ball mill. Use agate balls as the ball milling medium with a ball-to-material mass ratio of 30:1. Mill at a speed of 200r / min for 10min, perform preliminary mixing, and obtain uniform fine powder;
[0040] 2. Using monohydrated citric acid solid (molecular formula: C6H8O7·H2O) as a carbon source, weigh 2.5218g of monohydrated citric acid solid and mix it with the fine powder obtained in step 1 to obtain a light yellow powder; wherein the ratio of the amount of monohydrated citric acid to the total molar amount of transition metal elements is 1:1; putting the light yellow powder into a ball mill, using agate balls as the ball milling medium, with a ball-to-material mass ratio of 30:1, ball milling at a speed of 800r / min for 12h, and keeping the temperature at 40°C during the ball milling process to obtain a dry material; the particle size of the bulk intermediate is effectively reduced by ball milling, and a precursor with uniform composition is obtained;
[0041] 3. Transfer the dry material prepared in step 2 to a mortar and grind for 30 minutes to obtain a powdered precursor;
[0042] 4. The powdered precursor is transferred to a tubular furnace, and in a flowing high-purity argon protective atmosphere, the temperature is increased to 400°C at a rate of 2°C / min and maintained for 4 hours for pre-sintering, and then the temperature is increased to 600°C at a rate of 2°C / min and maintained for 6 hours for high-temperature calcination. The powdered precursor is naturally cooled to room temperature in the furnace to obtain sodium vanadium fluorophosphate, a positive electrode material for halogenated transition metal phosphate sodium ion batteries.
[0043] Example 1: This example is to prepare sodium vanadium fluorophosphate, a positive electrode material for a halogenated transition metal phosphate sodium ion battery, whose chemical formula is Na3V2(PO4)2F3. The preparation method of the material is carried out according to the following steps:
[0044] 1. At room temperature, weigh 0.9540g of anhydrous sodium carbonate, 1.4038g of ammonium metavanadate, 1.3800g of ammonium dihydrogen phosphate, and 0.6667g of ammonium fluoride according to the stoichiometric ratio of Na3V2(PO4)2F3 and transfer them to a ball mill. Use agate balls as the ball milling medium with a ball-to-material mass ratio of 30:1. Mill at a speed of 200r / min for 10min, perform preliminary mixing, and obtain uniform fine powder;
[0045] 2. Using monohydrated citric acid solid (C6H8O7·H2O) and ammonium citrate (C6H 11 NO7) Lewis acid-base pair is used as a carbon source and a reducing agent at the same time. 1.7651g of monohydrated citric acid solid and 0.8757g of ammonium citrate are weighed and mixed with the fine powder obtained in step 1 to obtain a light yellow powder; wherein the ratio of the total amount of Lewis acid-base pair to the total molar amount of transition metal elements is 1:1; the light yellow powder is put into a ball mill, agate balls are selected as the ball milling medium, the ball-to-material mass ratio is 30:1, and the ball milling is carried out at a speed of 800r / min for 12h. During the ball milling process, the temperature is maintained at 40°C to obtain a dry material; the particle size of the bulk intermediate is effectively reduced by ball milling, and a precursor with uniform composition is obtained;
[0046] 3. Transfer the dry material prepared in step 2 to a mortar and grind for 30 minutes to obtain a powdered precursor;
[0047] 4. The powdered precursor is transferred to a tubular furnace, and in a flowing high-purity argon protective atmosphere, the temperature is increased to 400°C at a rate of 2°C / min and maintained for 4 hours for pre-sintering, and then the temperature is increased to 600°C at a rate of 2°C / min and maintained for 6 hours for high-temperature calcination. The powdered precursor is naturally cooled to room temperature in the furnace to obtain sodium vanadium fluorophosphate, a positive electrode material for halogenated transition metal phosphate sodium ion batteries.
[0048] Figure 1 The XRD patterns of sodium vanadium fluorophosphate prepared in Comparative Example 1 and Example 1 are shown in Table 1. Figure 1 It can be seen that the sodium vanadium fluorophosphate prepared in Comparative Example 1 has non-negligible impurity phases, and these impurity peaks correspond to the standard PDF card of the Na3V2(PO4)3 phase after comparison. In the XRD spectrum of the sodium vanadium fluorophosphate prepared in Example 1, only the signal peak of the Na3V2(PO4)2F3 phase was observed, and these impurity phases were not detected, which proves that the generation of impurity phases is suppressed and high-purity sodium vanadium fluorophosphate is successfully prepared.
[0049] The sodium vanadium fluorophosphate prepared in Comparative Example 1 and the sodium vanadium fluorophosphate prepared in Example 1 were assembled into simulated button-type sodium ion batteries. The obtained button-type sodium ion batteries were subjected to electrochemical performance tests in a voltage range of 2.5 to 4.4V.
[0050] Figure 2 This is a rate performance diagram of sodium vanadium fluorophosphate prepared in Comparative Example 1 in a half-cell with sodium as the counter electrode. Figure 2 It can be seen that the sodium vanadium fluorophosphate prepared in Comparative Example 1 has poor rate performance and discharge capacity when the rate performance test is carried out in the voltage range of 2.5-4.4 V. Specifically, the battery assembled with the positive electrode material has an initial discharge capacity of 90 mAh / g at 10.0C.
[0051] Figure 3 The cyclic performance diagram of sodium vanadium fluorophosphate prepared in Comparative Example 1 at a current density of 10.0C in a half-cell with a sodium counter electrode. Figure 3 It can be seen that the cycle performance test is carried out in the voltage range of 2.5-4.4V, and the self-assembled half-cell of sodium vanadium fluorophosphate prepared in Comparative Example 1 is 105, 102, 100, 98, 94, 90, 85, 79, 66mAh / g at the rates of 0.2, 0.5, 1.0, 2.0, 5.0, 10.0, 15.0, 20.0, 30.0C, respectively. The material can be stably charged and discharged at a high current density for a long time, and only 53mAh / g of the discharge specific capacity is retained after 3000 cycles at a current density of 10.0C.
[0052] Figure 4 The constant current charge-discharge curve of sodium vanadium fluorophosphate prepared in Comparative Example 1 at 0.2C in a half-cell with sodium as the counter electrode. Figure 4 It can be seen that the sodium vanadium fluorophosphate positive electrode material prepared in Comparative Example 1 using only citric acid as the carbon source was subjected to constant current charge and discharge test in the voltage range of 2.5-4.4V. Its voltage platform was tilted and a low voltage platform was generated due to the Na3V2(PO4)3 impurity phase, which was caused by the loss of the halogen element F during the preparation process.
[0053] Figure 5 This is a rate performance diagram of sodium vanadium fluorophosphate, a positive electrode material for halogenated transition metal phosphate sodium ion batteries prepared in Example 1, in a half-cell with sodium as the counter electrode. Figure 5 It can be seen that the sodium vanadium fluorophosphate obtained by this preparation method exhibits good rate performance as a positive electrode material, which shows the feasibility of the strategy of obtaining pure phase halogenated transition metal phosphate sodium ion battery positive electrode materials by regulating Lewis acid-base pairs. Figure 5 It can be seen that the rate performance of the sodium vanadium fluorophosphate positive electrode material prepared in Example 1 is improved, and the charge and discharge at various currents show higher specific capacity. Specifically, the specific capacity of the button-type sodium ion battery obtained at 0.2, 0.5, 1.0, 2.0, 5.0, 10.0, 15.0, 20.0, and 30.0C rates is 119, 113, 110, 107, 101, 95, 89, 83, and 67 mAh / g, respectively. Constant current charge and discharge at a high current density of 10.0C can show a reversible capacity of 67 mAh / g.
[0054] Figure 6 This is a graph showing the cycling performance of sodium vanadium fluorophosphate, a positive electrode material for halogenated transition metal phosphate sodium ion batteries prepared in Example 1, at a current density of 10.0C in a half-cell with a sodium counter electrode. Figure 6 It can be seen that the material can be charged and discharged at a high current density for a long time and stably, and the discharge specific capacity of 60mAh / g is still retained after 3000 cycles at a current density of 10.0C.
[0055] Figure 7 This is the constant current charge-discharge curve of sodium vanadium fluorophosphate, a positive electrode material of halogenated transition metal phosphate sodium ion battery prepared in Example 1, at 0.2C in a half-cell with sodium as the counter electrode. Figure 7 It can be seen that the sodium vanadium fluorophosphate positive electrode material prepared in Example 1 using the Lewis acid-base pair as the carbon source is subjected to constant current charge and discharge test in the voltage range of 2.5-4.4V, and its voltage platform is more stable, and the low voltage platform caused by the Na3V2(PO4)3 impurity phase disappears.
[0056] Figure 8This is a SEM image of sodium vanadium fluorophosphate prepared in Comparative Example 1 in a half-cell with sodium as the counter electrode. Figure 8 It can be seen that the surface of the sodium vanadium fluorophosphate positive electrode material prepared in Comparative Example 1 using only citric acid as the carbon source has many holes, which indicates that the coating of the carbon coating layer is not dense enough, which will reduce the electronic conductivity of the electrode material.
[0057] Fig. 9 This is a SEM image of the sodium vanadium fluorophosphate, a positive electrode material for a sodium ion battery prepared in Example 1, in a half-cell with a sodium counter electrode. Fig. 9 It can be seen that compared with Comparative Example 1, the surface pores of the sodium vanadium fluorophosphate positive electrode material prepared in Example 1 using ammonium citrate and citric acid as carbon sources are reduced, and the carbon coating layer is dense, which improves the electronic conductivity of the electrode material. The improvement of electronic conductivity is also consistent with the Figure 4 , Example 1 Figure 7 The constant current charge and discharge curves of the obtained cathode materials confirmed each other, and the latter showed a smaller voltage polarization at a current density of 0.2C.
[0058] Fig.10 This is a TEM image of sodium vanadium fluorophosphate prepared in Comparative Example 1 in a half-cell with sodium as the counter electrode. Fig.10 It can be seen that the surface of the sodium vanadium fluorophosphate positive electrode material prepared in Comparative Example 1 using only citric acid as the carbon source has a thin and uneven conductive carbon coating layer, which causes the matrix material to be exposed to the outside and reduces the electronic conductivity of the electrode material.
[0059] Fig.11 This is a TEM image of the sodium vanadium fluorophosphate, a positive electrode material for a sodium ion battery prepared in Example 1, in a half-cell with a sodium counter electrode. Fig.11 It can be seen that compared with Comparative Example 1, the carbon coating layer on the surface of the sodium vanadium fluorophosphate positive electrode material substrate prepared in Example 1 using ammonium citrate and citric acid as carbon sources meets the thickness requirement of the surface carbon coating, so that the substrate material can exhibit better electronic conductivity while ensuring that it is completely coated with conductive carbon.
[0060] In the preparation process of the halogenated transition metal phosphate sodium ion battery positive electrode material, a carbon source having the function of a coating material and a reducing agent is added to make it uniformly coated on the surface of the material with a thickness in the range of 1 to 8 nm, and a Lewis base corresponding to the Lewis acid carbon source is introduced to stabilize the halogen atoms in the preparation process, so that it has high electronic conductivity and working voltage. In the preparation process, no solvent is needed for mixing, but the raw materials are directly dry mixed, which reduces the production cost. At the same time, more importantly, the side reaction between the solvent and other drugs and the volatilization of the halogen atoms are prevented.
[0061] The present invention synthesizes a uniformly carbon-coated matrix halogenated transition metal phosphate sodium ion battery positive electrode material with high specific energy. The material has high purity, plays a significant role in improving the working voltage of the material, can exert excellent rate performance and long cycle stability, and exhibits excellent electrochemical performance. The preparation operation of the present invention is simple, economical and practical, and has good reproducibility. The prepared material has high energy and power density and has broad application scenarios.
Claims
1. A halogenated transition metal phosphate sodium ion battery positive electrode material, characterized in that The material consists of a halogenated transition metal phosphate matrix and a conductive layer coated on its surface; the chemical formula of the halogenated transition metal phosphate is Na3M2(YO4)2O x X 3-2x ; 0≤x<1.5; M=V, Fe, Ti or Zr; Y=P, S or Si; X=F, Cl or Br; the surface-coated conductive layer is a carbon layer.
2. A method for preparing a halogenated transition metal phosphate sodium ion battery positive electrode material according to claim 1, characterized in that: The method proceeds as follows:
1. At room temperature, weigh the sodium source, transition metal M source, Y source and halogen source according to the stoichiometric ratio of the halogenated transition metal phosphate and transfer them to a ball mill for 10 min at 150-250 r / min or grind them in a mortar for 20-30 min to perform preliminary mixing to obtain uniform fine powder; 2. Weigh the carbon source and mix it with the fine powder of step 1 in a ball mill, and mill it at a speed of 400-1200 r / min for 8-12 hours to obtain a dry material; wherein the carbon source is an organic acid and a Lewis base corresponding to the organic acid; the organic acid is one or more of citric acid monohydrate, anhydrous citric acid and ascorbic acid, the Lewis base of citric acid is ammonium citrate, and the Lewis base of ascorbic acid is ascorbyl amine; 3. Transfer the obtained dry material to a mortar and grind it to obtain a powdered precursor; 4. The powdered precursor is transferred to a tubular furnace, pre-sintered in a flowing inert gas stream, and then continued to be heated to 500°C to 700°C for calcination for 5 to 12 hours. Finally, the powdered precursor is naturally cooled to room temperature as the tubular furnace temperature is cooled to obtain a halogenated transition metal phosphate sodium ion battery positive electrode material.
3. The method for preparing a halogenated transition metal phosphate sodium ion battery positive electrode material according to claim 2, characterized in that: The transition metal M source described in step 2 is an ammonium salt of transition metal M or an oxide of transition metal M; the Y source is NH4H2YO4 and / or (NH4)2HYO4; and the halogen source is NaX and / or NH4X.
4. The method for preparing a halogenated transition metal phosphate sodium ion battery positive electrode material according to claim 2 or 3, characterized in that: During the ball milling process described in step 2, the temperature is maintained at 35-55°C.
5. The method for preparing a halogenated transition metal phosphate sodium ion battery positive electrode material according to claim 2 or 3, characterized in that: The ratio of the amount of the carbon source in step 2 to the total amount of transition metal elements is 1:0.8-2.
5.
6. The method for preparing a halogenated transition metal phosphate sodium ion battery positive electrode material according to claim 2 or 3, characterized in that: The ball milling process described in steps 1 and 2 is carried out in air or argon protective atmosphere, the ball-to-material mass ratio is (10-50):1, and the ball milling medium is agate balls, ZrO2 balls or stainless steel balls.
7. The method for preparing a halogenated transition metal phosphate sodium ion battery positive electrode material according to claim 2 or 3, characterized in that: The pre-sintering temperature in step 4 is 350° C. to 450° C., and the pre-sintering time is 3 to 5 hours.
8. The method for preparing a halogenated transition metal phosphate sodium ion battery positive electrode material according to claim 2 or 3, characterized in that: The heating rate of the pre-sintering in step 4 is 2-10°C / min.
9. The method for preparing a halogenated transition metal phosphate sodium ion battery positive electrode material according to claim 2 or 3, characterized in that: The heating rate of calcination in step 4 is 2-10°C / min.
10. The method for preparing a halogenated transition metal phosphate sodium ion battery positive electrode material according to claim 2 or 3, characterized in that: The calcination temperature in step 4 is 550°C to 650°C, and the calcination time is 5 to 8 hours.
Citation Information
Patent Citations
Ionic compound and process for production thereof, and electrolytic solution and electrical storage device each utilizing the ionic compound
CN103370827A
Transition metal doped titanium manganese sodium phosphate / carbon composite positive electrode material, preparation thereof and application in sodium ion battery
CN110611080A
Preparation method of sodium vanadium trifluorophosphate serving as positive electrode material of sodium-ion battery
CN111606314A
Transition metal phosphate sodium ion battery positive electrode material and preparation method and application thereof
CN115036477A
Preparation method of carbon-coated sodium ferric manganese phosphate composite material
CN118289726A